Homocysteine plasma levels in psoriasis patients: our experience and review of the literature. (23rd March 2015) - Giannoni, M.; Consales, V.; Campanati, A.; Ganzetti, G.; Giuliodori, K.; Postacchini, V.; Liberati, G.; Azzaretto, L.; Vichi, S.; Guanciarossa, F.; Offidani, A.
Abstract Background People with psoriasis are at higher cardiovascular risk. Plasma levels of homocysteine over the normal range have been recognized as marker of cardiovascular risk. Psoriasis patients express higher levels of plasma homocysteine than healthy people. Objective Our study aims to investigate the correlation between homocysteinaemia, severity and duration of psoriasis and psoriasis arthritis, and to evaluate the effect of a 12‐week administration of a target therapy for psoriasis on homocysteinaemia. Methods Fifty‐two psoriasis patients (study group) submitted to different kind of therapy for psoriasis (biological, systemic not biological and topical) and 24 healthy Italian subject (control group) were evaluated for their plasmatic homocysteine levels, both at baseline (T0) and 12 weeks after they a specific therapy for psoriasis. Results A significant difference between the homocysteinaemia of psoriasis patients (mean 19.71 ± 11.16) and control group (13.90 ± 11.18), P < 0.05 (Fig. 1), was found at baseline (T0). The mean plasma levels of homocysteine were directly correlated with disease severity (P = 0.0401), but not with disease duration (P = 0.6018) or presence of arthritis (P = 0.6221) at baseline. None among the treatments administered to psoriasis patients caused a significant reduction in homocysteinaemia after 12 weeks of treatment. Conclusion Our results confirm that psoriasis patients with more severe disease, can have hyperhomocysteinaemia, without regard to disease duration or joint involvement. Hyperhomocysteinaemia is not influenced by a target therapy for psoriasis and it is as greater as psoriasis severity. However, limitation of our study is the relatively small number of cases. Homocysteine plasmatic levels should be advisable as a further independent risk factor for cardiovascular disease in psoriasis patients.